2020
DOI: 10.3390/e22111269
|View full text |Cite
|
Sign up to set email alerts
|

Canine Olfactory Detection of a Non-Systemic Phytobacterial Citrus Pathogen of International Quarantine Significance

Abstract: For millennia humans have benefitted from application of the acute canine sense of smell to hunt, track and find targets of importance. In this report, canines were evaluated for their ability to detect the severe exotic phytobacterial arboreal pathogen Xanthomonas citri pv. citri (Xcc), which is the causal agent of Asiatic citrus canker (Acc). Since Xcc causes only local lesions, infections are non-systemic, limiting the use of serological and molecular diagnostic tools for field-level detection. This necessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the field of medical diagnosis, dogs are known to detect specific conditions [ 16 ], but most are anecdotal reports instead of formal protocols designed to validate a diagnostic test for clinical use [ 17 ]. However, at least one study demonstrated that appropriate training, coupled with strict adherence to the scientific method, lead to consistent diagnosis of Clostridioides difficile infection in humans [ 18 ], and, more recently, a comprehensive method was published validating canine diagnosis of two plant pathogens of international concern [ 19 , 20 ]. Dogs detect and differentiate unique odors that result from the emission of volatile organic compounds (VOC) that constitute the “smell print” of the target [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of medical diagnosis, dogs are known to detect specific conditions [ 16 ], but most are anecdotal reports instead of formal protocols designed to validate a diagnostic test for clinical use [ 17 ]. However, at least one study demonstrated that appropriate training, coupled with strict adherence to the scientific method, lead to consistent diagnosis of Clostridioides difficile infection in humans [ 18 ], and, more recently, a comprehensive method was published validating canine diagnosis of two plant pathogens of international concern [ 19 , 20 ]. Dogs detect and differentiate unique odors that result from the emission of volatile organic compounds (VOC) that constitute the “smell print” of the target [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven dogs detected Asian citrus canker caused by X. citri pv. citri in seedlings, fruit orchards, packing houses, and even isolated bacterial cultures [73]. The dogs detected X. citri infections with a good sensitivity (73%) and specificity (99%).…”
Section: Caninesmentioning
confidence: 91%
“…Other studies have also demonstrated high rates of success in detection of plant pathogens causing laurel wilt disease in avocado trees [ 39 , 40 ]. Other researchers have demonstrated success with a citrus pathogen [ 41 , 42 ]. The current hypothesis assumes that, as with other diseased individuals, persons suffering from COVID-19 will exhibit a physiological change that manifests as a disease state related VOC profile, thereby allowing detection by a well-trained scent detection canine.…”
Section: Introductionmentioning
confidence: 99%